2017
DOI: 10.1002/andp.201600259
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection by active Fano‐sensor

Abstract: The optical properties and sensing performances of the molecular sensors based on plasmonic Fano-resonance (PFR) nanostructures have been numerically investigated in detail. The on-resonance sensor, in which the Fano-resonance position is overlapping with the absorption-band of the detected molecules perfectly, reveals a powerful ability to detect the molecules with a low concentration or thin thickness. By the bias-modulation of a single-layer graphene, the Fano-resonance position of the nanostructures can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As the wide application of multiplexing methods in various devices has developed, the research focus on optical Fano resonance has also expanded from single Fano resonance to multi-Fano resonance [35,36]. Multi-Fano resonance can be used efficiently in a multichannel biosensor and multi-band slow-light device.…”
Section: Introductionmentioning
confidence: 99%
“…As the wide application of multiplexing methods in various devices has developed, the research focus on optical Fano resonance has also expanded from single Fano resonance to multi-Fano resonance [35,36]. Multi-Fano resonance can be used efficiently in a multichannel biosensor and multi-band slow-light device.…”
Section: Introductionmentioning
confidence: 99%
“…The relative spectral position of these multipolar eigenmodes can be tailored by careful adjustment of the geometrical parameters. It has been demonstrated that the high-index all-dielectric metasurfaces have the capability of manipulating light-matter interaction with high efficiency, including polarization conversion [ 21 ], unidirectional scattering [ 22 ], generating vortex beam [ 23 ], and molecule sensing [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study may provide a further step in sensing, lasing, and nonlinear optics. High-quality (Q)-factor resonators play a key role in various fields of applications, such as nonlinear optics [1], sensors [2,3], lasers [4], chiral optical response [5], and optical switching [6]. The Fano resonance is one effective method to realize the high Q-factor resonance in metamaterials and metasurfaces [7,8].…”
mentioning
confidence: 99%